2009
DOI: 10.1007/s00018-009-8767-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction-induced amphiregulin upregulation mediates chemo-resistance and cell migration in HepG2 cells

Abstract: The aim of this study was to investigate the contribution of mitochondrial dysfunction to chemoresistance and migration of hepatoma cells. We found that inhibition of mitochondrial respiration and mitochondrial DNA (mtDNA) depletion resulted in induction of amphiregulin (AR) expression in HepG2 cells. Upon oligomycin treatment of HepG2 cells, the cytosolic Ca(2+) was significantly raised after 30 min, and the intracellular level of reactive oxygen species (ROS) was elevated 2.2-fold after 4 h. Moreover, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
0
37
1
Order By: Relevance
“…Therefore, they are considered a metabolic hallmark of cancer. Although the contribution of mitochondrial defects to cancer development, such as tumor angiogenesis, metastasis, and chemoresistance, has often been reported (6,10,11,(37)(38)(39), it is unclear how mitochondrial impairment regulates tumor progression. One plausible explanation is that an altered mitochondrial metabolism communicates with the nucleus through "mitochondrial retrograde signaling."…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are considered a metabolic hallmark of cancer. Although the contribution of mitochondrial defects to cancer development, such as tumor angiogenesis, metastasis, and chemoresistance, has often been reported (6,10,11,(37)(38)(39), it is unclear how mitochondrial impairment regulates tumor progression. One plausible explanation is that an altered mitochondrial metabolism communicates with the nucleus through "mitochondrial retrograde signaling."…”
Section: Discussionmentioning
confidence: 99%
“…55 Mitochondrial respiration defects in cancer cells cause activation of the Akt survival pathway and contribute to drug resistance through a redox mediated mechanism. 56 We also found that chemical impairment of the mitochondrial respiratory chain enhances cisplatin-resistance in human HepG2 cells through up-regulated expression and secretion of amphiregulin 57 and in human gastric cancer cells through a ROS-mediated regulation. 58 In addition, mtDNA copy number might affect hormone dependence in prostate cancer cells 59 and breast cancer cells.…”
Section: Mitochondrial Dysfunction Induced By Somatic Mtdna Alteratiomentioning
confidence: 91%
“…86 Moreover, mitochondrial dysfunctions caused by various respiration inhibitors have been shown to promote cell migration via ROS-enhanced b5-integrin expression in gastric cancer SC-M1 cells 58 or ROS-mediated upregulation of amphiregulin in human hepatoma HepG2 cells. 57 In addition to ROS, Ca 2þ was found to up-regulate amphiregulin and induce chemo-resistance and migration of human hepatoma HepG2 cells. 57 Moreover, elevated cytosolic Ca 2þ was found in cancer cells with mtDNA depletion by ethidium bromide 166 and was involved in the mtDNA depletion-induced expression of the invasive markers, cathepsin L and TGFb1 as well as the invasive phenotype.…”
Section: Activation Of Mitochondrial Retrograde Signaling Contributesmentioning
confidence: 99%
See 1 more Smart Citation
“…AREG overexpression provides self-sufficient growth and survival signals in lung carcinoma cells (15). AREG up-regulation has been associated with resistance to chemotherapy, such as doxorubicin and cisplatin in liver cancer cells (16,17) and cisplatin in breast cancer cells (18). AREG inhibits EGFR tyrosine kinase inhibitor (TKI)-induced apoptosis in NSCLC cells (15).…”
Section: Cetuximab (Cet) Restored the Sensitivity To Amrubicinol (Amentioning
confidence: 99%